Agricultural innovations for sustainable crop production intensification - Michele Pisante; Fabio Stagnari; Cynthia A. Grant (Italian Journal of Agronomy)
Sustainable crop production intensification should be the first strategic objective of innovative agronomic research for the next 40 years. A range of options exist (often very location specific) for farming practices, approaches and technologies that ensure sustainability, while at the same time improving crop production. The main challenge is to encourage farmers in the use of appropriate technologies,  and  to  ensure  that  knowledge  about  sound  production  practices  is  increasingly accepted and applied by farmers. There is a huge, but underutilized potential to link farmers’ local knowledge with science-based innovations, through favourable institutional arrangements.  The same  holds  for  the  design,  implementation  and  monitoring  of  improved  natural  resource management  that  links  community  initiatives  to  external  expertise.  It is also suggested that a comprehensive effort be undertaken to measure different stages of the innovation system, including technological adoption and diffusion at the farm level, and to investigate the impact of agricultural policies on technological change and technical efficiency. This paper provides a brief review of agronomic management practices that support sustainable crop production system and evidence on developments  in the selection of crops and cultivars; describes farming systems for crop which take a predominantly ecosystem approach; discusses the scientific application of ecosystem principles for the management of pest and weed populations; reviews the  improvements in fertilizer and nutrient management that explain productivity growth; describes the benefits and constraints of irrigation technologies; and suggests a way forward. Seven changes in the context for agricultural development are proposed that heighten the need to examine how innovation occurs in the agricultural sector.